Gender Sensitive Trade Union Policy to Address Workers in Informal Economy - Gelal, Prashu Ram (The Batuk, 2022)
The informal economy is diversified set of economic activities, enterprises, jobs and workers that are not regulated or protected by the state. It does not have any written rules or agreements and functioning merely on verbal understanding. There is no fixed wages or fixed hours of work and mostly relies on daily earnings and the workers are failed to come together and address their problems through an association or a group. The people working as small farmers, street vendors, hawkers, small traders, micro entrepreneurs, home based workers, cobblers, rag pickers, porters, laborers, artisans etc represent the informal sectors. Formal employment sector is limited both in size and varieties. On the other hand, informal economy is overcrowded by both the older and new entrant workers. Informal economy functioning outside government control and regulation, creates more vulnerability, precariousness, injustice and inequality in part of the millions of workers and even drags them to bondage and serfdom.